A STUDY ON THE EFFECTS OF AGOMELATINE ON FOOD INTAKE AND BODY WEIGHT IN RESTRAINT STRESS MODEL IN ADULT SWISS ALBINO MICE - SHANMUGAPRIYA S; S, Nivedhithaa; K, BHUVANESWARI (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: Agomelatine is a novel melatonin (MT) receptor agonist at MT 1 and 2, serotonin receptor antagonist and an effective chronobiotic agent. The study was designed to evaluate the effects of agomelatine on body weight and food intake in restraint stress model in adult Swiss albino mice. Methods: After the approval of Institutional Animal Ethics Committee, 40 male Swiss albino mice were randomly divided into four groups of 10 animals each; two were treatment groups which received 25 mg/kg (low dose) agomelatine, 50 mg/kg (high dose) agomelatine, standard group given trazodone and the control group administered the vehicle (1% hydroxyethyl cellulose [HEC]) intraperitoneally for the last 14 days in the 3 weeks study period. Chronic restraint stress was given for 4 hrs per day for all groups starting from day 0 to 21. Results: Using paired t-test, both 12 hrs (p=0.011) and 24 hrs (p<0.001) food intake in the high dose agomelatine group were significantly increased. Between groups using ANOVA test showed a statistically significant increase in food intake for this group when compared to the control group. Unlike the low dose agomelatine group (p=0.205), the mean body weight in the group treated with high dose agomelatine revealed a statistically significant rise compared to that of the control (p=0.001) in ANOVA test. Conclusion: High dose agomelatine was effective in antagonizing the body weight lowering effect of restraint stress in addition to amelioration of reduced food intake. The study has potentially brought out the additional therapeutic benefit of agomelatine in improving the altered feeding and body weight changes when used in the treatment of the depression.